Optimizing Certificate German (ZD) Test Preparedness with Regard to Form of Task - Walorczyk, Mariusz (Glottodidactica, 2009)
Optimizing Certificate German (ZD) Test Preparation with Regard to Task Form Placement and progress tests are used to provide optimum instruction. Experience with test task forms at various times in various situations increase task related skills and reduce test anxiety – closed tasks exercising recognition; open tasks production. Very important are skills in comprehending test task instructions and carrying them out. As an alternative to the more stressful schoolroom work, E-tests and CD-ROM work facilitate and stimulate preparation so long as the desired goals are kept in the forefront.